Migrációs attitűdök a magyar ki- és bevándorlási tendenciák tükrében - Palotai, Jenő; Jarjabka, Ákos (Közép-Európai Közlemények, 2017)
One of the main socio-economic challenges of today is migration. The first part of this study tries to define the concept of migration. It can be supposed that, as a result of the crisis in NorthAfrica and the Middle-East, the European countries should face the partial emigration or the filling up of their labour market. The current research examines the aspects of this domestic issue by analysing the composition of Hungarian emigrants and immigrants, and the decadal tendency of migration based on the data of Eurostat and the Hungarian Central Statistical Office. We highlight the problem arising from the different data of the two statistical offices and reveal those external and internal motivations which lead to emigration and immigration, considering the situation of the countries of destination as well. Based on the statistical data we also present the phenomena of concurrent homecoming. Furthermore, the effects of the current migration wave on Hungary are also analysed on the basis of the data gathered from the Office of Immigration and Nationality. Our study shows, that the migrants see Hungary as a transit country rather a country of destination.